Tungsten nitride nanoplates as an anode material for lithium ion batteries. Issue 1 (January 2016) - Park, Han-Chul; Kim, Si-Jin; Kim, Min-Cheol; Kim, Da-Mi; Park, Kyung-Won
Abstract: Well-defined mesoporous nanostructure electrodes have been known to have improved lithium ion reaction properties such as the lithium ion reaction, cyclability, and high rate performance. We suggest mesoporous tungsten nitride nanoplates prepared via a template-free synthesis for lithium-ion batteries. The as-prepared tungsten nitride (m-WN) exhibited a face-centered cubic WN phase, well-defined mesoporous structure. Furthermore, to investigate a formation mechanism of the well-defined mesoporous WN structure formed from two-dimensional WO3 nanoplates. Finally, the m-WN showed improved electrochemical reaction properties of lithium ions such as high specific capacity and high rate cycling performance due to low transport resistance and high lithium ion diffusion coefficient.